Levels of carnitine and acylcarnitines in reconstituted red blood cell samples washed with different concentrations of saline solutions (Colombia Medica, 2010)
Objective: To evaluate the percentage of carnitine and acylcarnitines remaining in red blood cells after washing them with different concentrations of saline solution.Materials and methods: Human blood samples were centrifuged and the blood cells were washed with different saline solutions. The final pellet was resuspended in PBS for card preparation and tandem mass spectrometry analysis.Results: It was found that carnitine, as well as short-chain, medium-chain, and long-chain acylcarnitines remain in red blood cells at average percentages of 19.3; 34; 34; and 32%, respectively. Significant differences were found for carnitine and acylcarnitine levels in blood washed with an isotonic solution compared to their levels using several hypotonic solutions (p